Can We Discharge Dynamically Risk-Stratified Low-Risk (Excellent Response to Treatment) Thyroid Cancer Patients After 5 Years of Follow-Up?. Issue 4 (April 2019) - Seejore, K.; Gerrard, G.E.; Gill, V.M.; Murray, R.D.
Abstract: Aims: The 2014 British Thyroid Association thyroid cancer guidelines recommend lifelong follow-up of thyroid cancer patients. This is probably unnecessary, can cause patient anxiety, is time consuming and places significant demand on National Health Service resources. It has been suggested that low-risk differentiated thyroid cancer (DTC) patients could be discharged to primary care once they are 5 years from diagnosis and treatment. The aim of this study was to investigate the potential safety of this practice. Materials and methods: In total, 756 patients with dynamically risk-stratified (DRS) low-risk/excellent response to treatment DTC treated over 2001–2013 in the Leeds region were followed after diagnostic surgery and the recurrence rate calculated. Results: The median follow-up time was nearly 10 years (5–17 years). Radiological recurrence occurred in 13/756 (1.7%) patients and was always preceded by raised thyroglobulin/ thyroglobulin antibody levels. In all 13 patients elevation of thyroglobulin occurred within 5 years of diagnosis. Two additional patients were found to have rising thyroglobulin at almost 9 and 10.5 years from diagnosis, although to date radiological recurrence has not been detected. Assuming these two patients developed recurrence with longer duration of follow-up, then 0.26% (2/756) of patients would not have their recurrence discovered within 5 years of diagnosis. To detect 100% of patients with a putative recurrence in our cohort would require 10.5 years of follow-up. Four patients had transiently raised thyroglobulin, which became undetectable within 2 years (in three patients), without any treatment and radiological recurrence was not discovered. Conclusion: Discharge of DRS low-risk DTC patients to primary care after 5 years of secondary care follow-up is reasonable, accepting that late recurrence may occur in a very small minority of individuals (0.26%, ∼1:400). A more cautious approach would be to continue monitoring for 10 years, although the frequency of assessments could be reduced with increasing duration of follow-up. Highlights: Recurrence occurred in 1.7% (13/756) of patients with DRS low-risk thyroid cancer. Radiological recurrence was preceded by rising thyroglobulin/thyroglobulin antibodies in all cases. Patients can be discharged at 5 years, accepting a small late recurrence in ∼1:400. If discharge was at 10.5 years, 100% potential recurrences would be detected.